2010
DOI: 10.1186/1471-2458-10-324
|View full text |Cite
|
Sign up to set email alerts
|

Screen-based activities and physical complaints among adolescents from the Nordic countries

Abstract: BackgroundA positive association between time spent on sedentary screen-based activities and physical complaints has been reported, but the cumulative association between different types of screen-based activities and physical complaints has not been examined thoroughly.MethodsThe cross-sectional association between screen-based activity and physical complaints (backache and headache) among students was examined in a sample of 31022 adolescents from Denmark, Sweden, Norway, Finland, Iceland and Greenland, as p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
116
1
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(133 citation statements)
references
References 18 publications
12
116
1
4
Order By: Relevance
“…Computer use was measured by asking: "About how many hours do you spend using a computer (Internet, chatting, e-mailing, homework etc.)?" All questions had the same nine responses categories separately for weekdays and weekends: None at all; About half an hour a day; About 1 hour a day; About 2 hours a day; About 3 hours a day; About 4 hours a day; About 5 hours a day; About 6 hours a day; About 7 or more hours a day (3). Using the recommendations of the American Academy of Pediatrics (29) they were classified into three categories as follows: 1 -active less than 2 hours per day; 2 -active 2-3 hours per day; 3 -active more than 3 hours per day.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Computer use was measured by asking: "About how many hours do you spend using a computer (Internet, chatting, e-mailing, homework etc.)?" All questions had the same nine responses categories separately for weekdays and weekends: None at all; About half an hour a day; About 1 hour a day; About 2 hours a day; About 3 hours a day; About 4 hours a day; About 5 hours a day; About 6 hours a day; About 7 or more hours a day (3). Using the recommendations of the American Academy of Pediatrics (29) they were classified into three categories as follows: 1 -active less than 2 hours per day; 2 -active 2-3 hours per day; 3 -active more than 3 hours per day.…”
Section: Methodsmentioning
confidence: 99%
“…A high level of screenbased sedentary behaviour is related to different kind of physical problems (2,3) or psychological complaints (4). According to findings of the international Health Behaviour in School-aged Children (HBSC) study, age differences were observed.…”
Section: Introductionmentioning
confidence: 99%
“…There is also strong evidence, however, that EM use may be related to a variety of problem behaviors in adolescence, such as internet addiction (Adiele and Olatokun 2014), shortened sleep duration, poorer diet quality, lower physical activity levels, weight gain (Jackson et al 2011;Chahal et al 2013), poor school performance (Mößle et al 2010), loneliness (Deniz 2010), depression and social anxiety symptoms (Becker et al 2013), and increased likelihood of physical complaints (Torsheim et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Such screenbased activities have been shown to be associated with backache and headache among adolescents [31].…”
mentioning
confidence: 99%